Functional activity limitation of leprosy cases in an endemic area in Indonesia and recommendations for integrated participation program in society. - Sri Linuwih Menaldi; Melinda Harini; Nelfidayani Nelfidayani; Yunia Irawati; Steven Setiono; Luh Karunia Wahyuni; Tri Rahayu; Gitalisa Andayani; Dewi Friska; Boya Nugraha (Public Library of Science (PLoS), 2022)
Background Leprosy continues to be a health problem in Indonesia, with incidence reaching over 10,000 new cases by 2021. Leprosy-related disabilities cause limitation of patients' activity and participation in social activities. To date, no studies have been conducted in Indonesia which investigates disability in terms of bodily function, structure impairment, limitations in performing daily activities, and restrictions in participation in social activities in leprosy patients. This study is aimed to determine the demographic and clinical characteristics that might affect functional activity limitations of leprosy patients in endemic areas in Indonesia. Methods and findings A cross-sectional study was conducted on 267 retrospectively-diagnosed cases of leprosy. The Screening of Activity Limitation and Safety Awareness (SALSA) scale was used to measure functional activity limitation, which comprises five domains: vision, mobility, self-care, work with hands, and dexterity. Differences among variables were evaluated using Kruskal-Wallis and Mann-Whitney test. The mean age of participants was 51.89±13.66 years, the majority of which were men (62.5%), uneducated (48.3%), and classified as type 2 in the World Health Organization (WHO) disability grading for hands and feet (66.3% and 68.2%, respectively). Assessment using the SALSA Scale showed 28.5% of subjects were without limitation, 43.8% with mild limitation, 13.5% with moderate limitation, 9.4% with severe limitation, and 4.9% with extreme limitation. Significant differences in the total SALSA Scale were found between age groups (p = 0.014), educational level (p = 0.005), occupation (p<0.001), and WHO disability grades (p<0.001). Multivariate analysis showed that the most significant factor influencing the total score of SALSA was disability grading for feet (score = 0.31, p <0.001) followed by occupational status, disability grading for eyes, and age. Limitation of functional activity was significantly correlated to becoming unemployed with the odds 2.59. Conclusion People affected by leprosy are prone to have functional activity limitation, especially the elderly, uneducated, unemployed and those with multiple disabilities. If they can overcome their barriers in functional activities, they will have better occupational opportunities.